Meta-Analysis: Effectiveness of Electroacupuncture in Reducing Anxiety and Depression - Yessy Widhi Astuti; Bhisma Murti; Hanung Prasetya (Indonesian Journal of Medicine, 2023)
Background:  Anxiety and depression can happen to anyone, especially in patients with certain diseases. Anxiety and depression can affect activity, and reduce quality of sleep, and life. Electroacupuncture is one of the therapies with small side effects to reduce anxiety and depression and provide a sedative effect. This study aims to analyze and estimate the effectiveness of electroacupuncture therapy to reduce anxiety and depression in patients based on the results of similar studies.Subjects and Method:  This study used a systematic review and meta-analysis based on PICO, Population: Patients. Intervention: Electroacupuncture. Comparison: NonElectroacupuncture. Outcome: Decreased anxiety and depression. Data were obtained from Google Scholar, PubMed, Science Direct Hindawi, BMC, and Springer Link databases from 2010 to 2023. The search process used the keywords "electroacupuncture" AND "anxiety" OR "depression" AND "RCT". Article selection used the PRISMA flowchart and the results were analyzed using Review Manager 5.3 software.Results: 9 articles from Brazil, Spain, Hong Kong, and China with a sample size of 458 subjects were used in a meta-analysis of the effectiveness of electroacupuncture to reduce anxiety. And as many as 11 articles from Brazil, Spain, Hong Kong, and China with a sample size of 555 subjects were used for a meta-analysis of the effectiveness of electroacupuncture to reduce depression with an RCT study design. The results of the meta-analysis showed that patients who received electroacupuncture therapy intervention experienced an average of 0.68 units lower in anxiety (SMD=0.68; 95% CI= 1.04 to 0.33; p=0.001) and 0.51 units lower in depression (SMD =0.51; 95% CI= 0.86 to 0.16; p=0.004) compared to the group without electroacupuncture therapy.Conclusion:  Electroacupuncture therapy reduces anxiety and depression.Keywords:  acupuncture, electroacupuncture, anxiety, depressionCorrespondence:  Yessy Widhi Astuti, Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: widhiyessy123@gmail.com. Mobile: +6285754174209.Indonesian Journal of Medicine (2023), 08(03): 295-309https://doi.org/10.26911/theijmed.2023.08.03.07